LEGAL REGULATION OF THE PROVIDING THE MEDICINAL PRODUCTS IN THE CONDITIONS OF WAR (THEORETICAL AND LEGAL REVIEW) - Kostytsky, Vasyl; Suhodolska, Anastasiia (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Purpose: to investigate legal acts, national and international standards of law, theoretical-legal, ethical, moral principles of providing medicinal products in emergency situations and in conditions of war. The methodological basis of the research consists of comparative legal methods, special legal methods, synthesis and generalization, observation, general scientific methods of analysis. Results: on the basis of a complete and comprehensive study the problems of the implementation of the right norms in the field of provision of medicinal products, develop systematic conclusions and proposals that determine the ways of improving the functioning of the legal mechanism in this field of social relations with the aim of determining the principles and conditions of compliance by the state with the main constitutional guarantees and ratified by the Verkhovna Rada international treaties, taking into account the study of the basic rights and responsibilities of a person and a citizen, as well as the powers of executive authorities, military-civilian administration bodies, military doctors, and the rights of volunteers in conditions of emergency or martial law in Ukraine. Discussion: it was established that the legal regulation of the provision of medicines requires a comprehensive analysis of the legislation and the practice of its implementation and application, as well as the development of a single mechanism for the implementation of the provision of medicines, taking into account the local peculiarities of the implementation of the law and the functioning of state authorities and local self-government bodies during emergency events or martial law. Provision of medicinal products is one of the components of the observance of basic human and citizen rights, in particular the right to health care and medical assistance. It is obvious that the observance of the rights, freedoms and legitimate interests of citizens can be properly implemented under the condition of the development and implementation of a single legal mechanism of legal regulation in an emergency situation or under martial law conditions. This mechanism should be aimed at ensuring a number of social guarantees for a person, in particular, the provision of medicines. It is important that each participant feels the degree of his personal responsibility and assumed political and moral obligations, as well as legal obligations in accordance to it participation in the process.